18.8k views
21 votes
Enter your answer and show all the steps that you use to solve this problem and write your final answer in a factored form in the space provided.

Simplify:
(9x^3 + 2x^2 − 5x + 4) − (5x^3 − 7x + 4)

User Guinny
by
4.3k points

2 Answers

5 votes
  • 9x³+2x²-5x+4-(5x³-7x+4)
  • 9x³+2x²-5x+4-5x³+7x-4
  • 9x³-5x³+2x²-5x+7x+4-4
  • 4x³+2x²+2x
  • 2x(2x²+x+1)
User Praneet Nadkar
by
5.4k points
9 votes

Explanation:

f (x) - g (x) = 9 x³ + 2 x² - 5 x + 4 - ( 5 x³ - 7 x + 4 ) =

9 x³ + 2 x² - 5 x + 4 - 5 x³ + 7 x - 4 =

9 x³ - 5 x³ + 2 x² - 5 x + 7 x + 4 - 4 =

4 x³ + 2 x² + 2 x =

2 x ∙ ( 2 x² + x + 1 )

User Callmejeevan
by
4.5k points